2012
DOI: 10.1186/1757-7241-20-16
|View full text |Cite
|
Sign up to set email alerts
|

Effect of feedback on delaying deterioration in quality of compressions during 2 minutes of continuous chest compressions: a randomized manikin study investigating performance with and without feedback

Abstract: Background: Good quality basic life support (BLS) improves outcome following cardiac arrest. As BLS performance deteriorates over time we performed a parallel group, superiority study to investigate the effect of feedback on quality of chest compression with the hypothesis that feedback delays deterioration of quality of compressions. Methods: Participants attending a national one-day conference on cardiac arrest and CPR in Denmark were randomized to perform single-rescuer BLS with (n = 26) or without verbal a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
2

Year Published

2012
2012
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 14 publications
1
12
2
Order By: Relevance
“…This correlates well with the results of a number of previous studies, indicating that fatigue manifests under the 2010 guidelines at a similar time point to that of previous ERC guidelines 7 9 13 14. It is, however, in contrast with a recent study conducted on a smaller cohort by Lyngeraa et al , which suggested that the quality of CPR was maintained throughout 2 min of CPR delivery by rescuers using the 2010 ERC guidelines 15.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…This correlates well with the results of a number of previous studies, indicating that fatigue manifests under the 2010 guidelines at a similar time point to that of previous ERC guidelines 7 9 13 14. It is, however, in contrast with a recent study conducted on a smaller cohort by Lyngeraa et al , which suggested that the quality of CPR was maintained throughout 2 min of CPR delivery by rescuers using the 2010 ERC guidelines 15.…”
Section: Discussionsupporting
confidence: 88%
“…While previous studies highlight that rescuers following pre-2010 guidelines suffered from as great as a 55% increase in compressions of insufficient depth between minutes 1 and 2, the increases in aberrant compressions described within this study are far more modest (we identified a comparatively minor 7% increase) 7 9 13 14. This must be seen in the context of the overall quality of rescuers' CPR delivery within our study.…”
Section: Discussioncontrasting
confidence: 51%
See 1 more Smart Citation
“…(1)(2)(3)(4)(5)(6)(7)(8) However, at least one study has highlighted the potential problems of reliance on devices, and another study has concluded that there was no benefi t derived among trained responders. (9,10) In these studies, the feedback devices were attached to an automated external defi brillator (AED) or paired with a phone application; some were also hospital-based and could not be readily carried around by laymen. Also, in many of these studies, mixed results were observed in the CPR performance of healthcare workers or experienced life-savers.…”
Section: Introductionmentioning
confidence: 99%
“…Use of a feedback system during chest compressions might motivate exhausted rescuers to improve their performance of chest compressions. However, a recent simulation study showed that live feedback had little effect on the rescuers' ability to maintain compression quality during uninterrupted 2 min chest compressions [16]. Unless objective parameters such as end-tidal CO 2 , intraarterial pressure, or central venous saturations are available, this subjective method seems to be the most practical option.…”
Section: Discussionmentioning
confidence: 97%